Family-Based Education to Improve Health Literacy and Treatment Adherence Among T2DM Patients - Kurnia, Anih; Betty Suprapti; Aneng Yuningsih; Ai Rahmawati; Ana Ikhsan H (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
This community service program aimed to improve health literacy, treatment adherence, and the quality of life among patients with type 2 diabetes mellitus (T2DM) through a family-based education model. The intervention was conducted over six months at three community health centers (Puskesmas) in Tasikmalaya City: Kahuripan, Tamansari, and Cihideung. A total of 84 T2DM patients and their families participated in interactive educational sessions, including animated videos, family coaching, glucometer training, and a practical family handbook. Pre and post-tests were conducted using the SCPI (Skills, Confidence & Preparedness Index) instrument. The results showed significant improvements in health literacy (p = 0.000), family involvement (p = 0.000), and dietary adherence (p = 0.000). However, blood glucose levels did not significantly improve statistically (p = 0.305), indicating the need for a longer intervention period to achieve clinical outcomes. This program demonstrates the value of integrating family involvement and low-literacy-friendly media into diabetes education and offers a replicable model for other community-based health programs.